SOUTH CHINA SEA: CONFLICT, CHALLENGE, AND SOLUTION - Winanda kusuma; A. Cery Kurnia; Rio Armanda Agustian (Lampung Journal of International Law, 2021)
The South China Sea is a strategic marine area in terms of natural resource potential and international trade routes. For decades, territorial disputes have occurred with peaceful solutions from regional organizations, international courts, and even contributions from outside the claimant state. This paper examines the efforts made to contribute to a peaceful solution to disputed states of claims. The achievement of a peaceful solution, the shortcomings of the peaceful solution to the proposed peaceful solution's chronology. This research is normative juridical research that is historical descriptive in nature. The South China Sea Dispute arises from China's actions regarding its map of its maritime territories that do not comply with international maritime law. Regulations regarding the method of drawing deep-sea boundaries under international maritime law are violated in this act. Negotiation efforts in finding conflict solutions in regional organizations, state leadership meetings, informal meetings of claim state policymakers, and efforts to file claims by the Philippines at permanent court arbitration have been carried out. China's action that does not recognize the Philippine lawsuit decision poses a challenge to international maritime law and its member countries. A complete peaceful solution must be sought immediately when Softlaw and hard law must comply with the claiming state.